Patient satisfaction with general practice in Scotland 2011/12 to 2021/22 - David Henderson; Eddie Donaghy; Kieran Sweeney; Bruce Guthrie; Andrew G. H. Thompson; Harry H. X. Wang; Stewart W. Mercer (PLoS ONE, 2025)
Background The Scottish Government introduced the first phase of a new General Practice (GP) contract in 2018, aiming to transform primary care and address health inequalities. However, the impact of these changes on patient satisfaction is unclear. Aim To assess temporal changes in overall patient satisfaction, and satisfaction with access and consultation quality, in general practice between 2011/12 and 2021/22, focusing on disparities across sociodemographic groups. Design and Setting Analysis of biennial national Health and Care Experience (HACE) survey data from patients in Scotland, spanning six survey waves. Methods Descriptive analyses of trends in patient satisfaction, access, and consultation quality. Disparities in deprivation were measured by the Relative Index of Inequality (RII). Results Overall patient satisfaction with general practice declined significantly over the 10 years, with mean positive scores dropping from 90.1% in 2011/12 to 70.5% in 2021/22. Satisfaction was lower in patients living in more deprived areas at all time points, and the gap between the most and least deprived populations widened over time, with the RII increasing from 1.05 (95% CI 1.04–1.06) in 2011/12 to 1.12 (95% CI 1.08–1.15) in 2021/22. Overall satisfaction and access satisfaction had the most pronounced declines, especially among younger patients and those with multiple long-term conditions. In contrast, consultation quality measures (whether patients felt listened to and had enough time during consultations) remained largely stable with only slight declines observed. Conclusion Satisfaction overall, and with access to GP consultations, steadily declined between 2011/12 and 2021/22, with a more pronounced decrease following the COVID-19 pandemic, particularly among the most deprived and complex patients. Although the new GP contract was introduced during this period, it does not appear to have significantly impacted these downward trends. These findings highlight the need for focused efforts to improve patient satisfaction, especially in disadvantaged populations, as the contract evolves.